Blended learning in Higher Education: the scenery of national and international research (Research, Society and Development, 2020)
The thematic focus of this study is the Systematic Literature Review (RSL) movement carried out in Education Research, whose focus of the RSL practice was to contemplate the reference axes of the investigation, embodied in the possibilities found in the theoretical-conceptual-methodological context of the Blended Learning (BL), at the national and international level based on the referring researchers on the topic; in order to list educational research on the subject in Higher Education. The results show the BL beyond a pedagogical-technological tendency to think about the training spaces in Higher Education, connecting and questioning what, with what, how and who to teach/train. It is essential to highlight the little scientific production in national journals on the subject and, consequently, rare Brazilian theorists addressing BL in education, at any level of education. The BL is today one of the most accentuated trends in the teaching and learning process, reconfiguring the educational possibilities of training spaces (face-to-face and virtual).